Green Beans Cultivation Using Mice Pets Control to Improve the Quality of Bintaro Fruit Extract - Ajeng Embri Legawati; Nur Azizah; Achmad Ramadhan (OJS Universitas Muhammadiyah Gresik, 2018)
Green beans cultivation technology using mice pets control has been implemented in the Gluranploso village, Benjeng Gresik. The implementation of the technology performed for 2.5 months from August to October 2017. The purpose of the implementation is aimed to reduce the dependence of farmers on the use of chemical pesticides so that the farmers are aware of the negative impact of chemical pesticides. Assessing the impact of the utilization of Bintaro fruit and fruit extracts to explore ways of making Bintaro as a natural biopesticide to overcome rat attack on green bean plants in the Gluranploso village. Pest control mice can reduce the rate of loss of the crops more effectively and efficiently. Finally, with the use of those natural resources as a biopesticide material can also maintain the environmental balance